Analisis Faktor-Faktor Yang Mempengaruhi Pembangunan Ekonomi Daerah Provinsi Sumatera Utara - Afriza Ulfa Ritonga; Nurhayati Harahap (Jurnal Penelitian Ilmu Ekonomi dan Keuangan Syariah, 2024)
Economic development means the process of increasing total income and per capita income, taking into account population growth, significant changes in the country's economic structure, and equal distribution of income between residents. Economic growth is an inseparable part of economic development; Economic growth results in economic growth and vice versa, economic growth increases the speed of the economic development process. Economic growth is the process of increasing the production capacity of the economy which is reflected in an increase in national income. A country is claimed to be in economic growth when its real GDP is higher. Developing countries.